Damselflies of the genus Argia of the Guiana Shield (Odonata: Coenagrionidae) - Garrison, Rosser W.; Ellenrieder, Natalia Von (Zootaxa, 2015)
This revision of all 21 species of Argia known to occur within the Guiana Shield includes descriptions of new species, synonymies, keys to both sexes based primarily on morphology of caudal appendages and genital ligula in males and of the mesostigmal plates in females, diagnoses accompanied by illustrations and distribution maps for all species. Twelve new species are described: A. appendiculata (Holotype ♂: Venezuela, Amazonas State, Cerro de la Neblina, Base Camp, 0°50’ N, 66°10’ W, 18 ii 1985, P.J. & P.M. Spangler, R.A. Faitoute leg., in USNM), A. azurea (Holotype ♂: Guyana, Potaro-Siparuni Region, Kaieteur Ravine, about 5°10’ N, 59°28’ W, 11 iv 1912, J.M. Geddes leg., in UMMZ), A. cuneifera (Holotype ♂: Venezuela, Amazonas State, Cerro de la Neblina, Base Camp, 0°50’ N, 66°10’ W, 20–24 iii 1984, O.S. Flint, Jr. & J.A. Louton leg., in USNM), A. deceptor (Holotype ♂: French Guiana, Cayenne Department, Régina Commune, Saut Athanase, 4°10’59" N, 52°20’6" W, 9 x 2001, L. Juillerat leg., in MHNN), A. donnellyi (Holotype ♂: Venezuela, Bolívar State, small marsh and creek on plateau surface above Coñac River, 10 km E of El Paují; about 4°31’ N, 61°31’ W, 5 viii 1990, RWG leg., in CSCA), A. gemella (Holotype ♂: Brazil, Amazonas State, Reserva Ducke, 26 km E Manaus (3°0’15’’ S, 59°56’23’’ W, 120 m), 2–4 ii 1979, O.S. Flint Jr. leg., in USNM), A. guyanica (Holotype ♂: Venezuela, Amazonas State, Cerro de la Neblina, Camp IV, 0°58’ N, 65°57’ W, 15–18 iii 1984, O.S. Flint, Jr. leg., in USNM), A. joallynae (Holotype ♂: Venezuela, Bolívar State, Canaima, palm marsh, 6°14’30" N, 62°50’53" W, 22–25 ix 1980, R.W. & J.A. Garrison. leg., in CSCA), A. loutoni (Holotype ♂: Brazil, Amazonas State, Purus River, Nova Olinda, about 3°30’ S, 57°56’ W, 6 ii 1979, O.S. Flint, Jr. leg., in FSCA), A. meioura (Holotype ♂: Brazil, Amazonas State, Manaus, about 2°55’ S, 59°59’ W, 26 vi 1922, J.H. Williamson & J.W. Strohm leg., in UMMZ), A. palmata (Holotype ♂: Brazil, Amazonas State, Manaus, about 5 miles N of Flores on route to Campos Sales, small creek in virgin forest, about 3°0’S, 60°1’ W, 15 vi 1922, J.H. Williamson & J.W. Strohm leg., in UMMZ), and A. recurvata (Holotype ♂: Venezuela, Amazonas State, San Carlos de Río Negro, 1°55’ N, 67°4’ W, 97 m, 14–21 iii 1984, J. De Marmels leg., in MIZA). The status of Argia impura Rambur, 1842, is discussed and the following nomenclatural changes are proposed: Argia stigmatica Navás, 1934 and A. umbriaca Fraser, 1946 are considered junior synonyms of Argia indicatrix Calvert, 1902, and Argia eliptica Selys, 1865 and A. icterica Navás, 1934 are considered junior synonyms of A. oculata Hagen in Selys, 1865.